Władza i prawo. Studium z hermeneutyki politycznej - Paradowski, Ryszard (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2004)
Political position of the Catholic Church in Poland, eclectic nature of constitutional principles of the 1997 Constitution as well as persistent attempts made to acknowledge the Christian character of the European Union pose a question about the actual meaning of Christian values as well as their attitude to democratic values and principles. Addressing this question the author analyzes the notion of authority and law in the Old and New Testament. He refers to the authoritarian interpretation of these notions in Catholicism and in particular to the secondary and inferior commandment of loving ones’ neighbor, which is subordinated to the commandment of unconditional subjection to the Highest Authority.